Biochar mitigates the N2O emissions from acidic soil by increasing the nosZ and nirK gene abundance and soil pH. (1st February 2020) - Aamer, Muhammad; Shaaban, Muhammad; Hassan, Muhammad Umair; Guoqin, Huang; Ying, Liu; Hai Ying, Tang; Rasul, Fahd; Qiaoying, Ma; Zhuanling, Li; Rasheed, Adnan; Peng, Zhang
Abstract: Nitrous oxide (N2 O) is a pervasive greenhouse gas, and soil management practices greatly affect its release into the atmosphere. Soil pH management (particularly increasing the pH) using biochar can seriously affect soil N2 O emissions. The current incubation experiment was conducted to explore the response of N2 O emissions from acidic soils using various doses of biochar. Soil with a pH of 5.48 was treated with rice straw biochar at different doses (0%, 1% and 2%) and incubated with 60% water-filled pore spaces (WFPS). The experiment was conducted in a completely randomized design (CRD) with three replications. The soil N2 O emissions, pH, NH4 + -N, NO3 − -N, microbial biomass carbon (MBC), and nosZ and nirK gene abundance were determined at various intervals throughout the study. The biochar application (2%) increased the soil pH (from 5.48 to 6.11), triggered the transformation of nitrogen, and augmented the abundance of nosZ and nirK genes. Higher magnitudes of cumulative soil N2 O emissions (48.60 μg kg −1 ) were noted in the control (no biochar) compared to 1% (28.10 μg kg −1 ) and 2% (14.50 μg kg −1 ) biochar application. The 2% biochar application more effectively decreased the soil N2 O emissions, mainly because of the increased nosZ and nirK gene abundance at higher soil pH levels. The findings suggest that the amelioration of acidic soil with rice straw biochar can considerably control soil N2 O emissions by elevating the soil pH and the abundance of nosZ and nirK genes. Highlights: Increase in soil pH and reduction in N2 O emissions by biochar applications. Biochar application leads to reduction microbial biomass carbon. Biochar application rates differed for soil mineral N. The rates of biochar application results in differences in nosZ and nirK genes abundance.